Pengaruh Karakteristik Anggaran terhadap Rentabilitas Ekonomis pada Koperasi Unit Desa (KUD) di Kabupaten Buton, Sulawesi Tenggara - Husin (Jurnal Aplikasi Manajemen, 2009)
Purpose of research expected to know empirical evidence about there or there is no there are influence significant between budget characteristic to economic rentability at koperasi unit desa (KUD) in kabupaten buton. Analytical method applied in this research is path analysis to know budget characteristic influence as independent variable with elements that is accurate participation of compilation (X1), level of clarity (X2), feedback (X3) and level of difficulty (X4) to economic rentability. Result of calculation inferential line analysis that budget characteristic influential significant with economic rentability of koperasi unit desa (KUD) in kabupaten buton.